PECULIARITIES OF ETIOPATHOGENESIS, DIAGNOSIS AND TREATMENT OF CYSTITIS IN PAEDIATRIC PATIENTS - Шикунова, Яна Владимировна; Гудков, Александр Владимирович; Слизовский, Григорий Владимирович; Геренг, Елена Андреевна; Балаганский, Дмитрий Анатольевич (Mother and Baby in Kuzbass, 2016)
Cystitis is one of the most widely spread pathologies in the practice of any paediatric urologist. The objective of the research is to identify peculiarities of etiopathogenesis, morphology of the bladder wall in acute bacterial cystitis and to evaluate efficacy of treatment of the chronic bullous cystitis in children. Material and methods. The study was conducted on 40 albino rats. Acute bacterial cystitis was simulated in rats. Ceftriaxone was used in the treatment group. No treatment was performed in the control group. The clinical study enrolled 30 children with chronic bullous cystitis. ELISA blood test and PCR urine test for infections, cystoscopy with biopsy were performed. Results and discussions. In case of acute bacterial cystitis development in animals, the pathological process involves all layers of the bladder. Microbe eradication took place on the 10th day of antibiotic treatment; however, the bladder wall still had signs of inflammation. In 12 girls (40 %) elevation of IgM to Ureaplasma urealyticum was observed, in 9 girls (30 %) to Chlamydia trachomatis, in 9 (30 %) to Mycoplasma hominis, in 100 % to HSV and CMV. PCR urine test in 6 cases (20 %) demonstrated presence of Mycoplasma hominis, in 6 (20 %) of Ureaplasma urealyticum. Escherichia coli in biopsy samples was found in 6 girls (20 %). In 5 cases (16,7 %) Streptococcus viridians was found, in 4 (13,3 %) – Staphylococcus saprophyticus, in 2 (6,7 %) – Enterococcus faecalis, in 3 girls (10 %) – mixed infection (Escherichia coli + Staphylococcus saprophyticus) was found. Antibiotics were added to the therapy based on the susceptibility of microbes found in the process of biopsy samples inoculation taking into account infections identified and immunomodulatory therapy. For the period of 6 months, 2 children (6,7 %) had exacerbation of chronic cystitis. Conclusion. Approach to diagnosis and treatment of children with cystitis should be complex and comprehensive.